Syntax Device and Unit Disorder in Children with Mental Retardation: A Neurolinguistic Perpspective on Language Learning Innovations and Progressive Education - Fathiaty Murthado; Fernandes Arung; Endry Boeriswati; Silfia Rahman (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2021)
This study aimed at obtaining information from neurolinguistic perspective about how children with mental retardation experience language learning by focusing on syntax device and unit disorder. With a qualitative paradigm, this study involved three children with mental retardation aged 17, 12, and 13 years at a special school in East Jakarta. Data in the form of utterances from three children with mental retardation through communication interactions were collected and produced 12 recordings which were then analyzed by apply-ing content analysis technique. The results of this study indicated that there were 151 errors in the form of syntax unit disorder, and the most errors were in the form of the phrase unit, amounting to 61 errors. In terms of syntax device disorder, 37 errors were found, of which the most errors were in intonation defects, amounting to 12 errors. The conclusion of the study is that children with mental retardation experience language disorders in the form of syntax defects because they are influenced by neurological disorders. How-ever, we see that these findings should not be standard benchmarks for mental and neurological disorders, so we argue that the defects in the syntax devices and units exhibited by children with mental retardation should be seen as a componential model of language issue on which their language development should be more focused on the meaning they get from information. In other words, we cannot just stick to the results which state that children with mental retardation have language difficulties but we must focus more on what they can understand as meaningful language to them. Therefore, we recommend trying to approach it with the concept of componential model of language that may be applicable with some technologies as innovative teaching and learning for teachers as well as progressive education for the children with mental retardation for their language learning experiences.